Kesantunan Berbahasa dalam Interaksi Pembelajaran Bahasa Indonesia Mahasiswa STIE Sakti Alam Kerinci - Suci Marselina (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
Abstract The purpose of this study was to describe the form of language politeness in student-to-student interaction during Indonesian language learning presentation activities in class IIIA of the STIE Sakti Alam Kerinci Accounting Study Program. identification of data, grouping data based on its type both from the results of recording and recording Interpretation of forms of language politeness in the learning process in class IIIA Accounting Study Program STIE Sakti Alam Kerinci according to Leech's politeness theory, namely a. The Maxim of Wisdom. b. Generosity Maxim c. Maxim of Award d. Simplicity Maxim e. Maxim of Consensus f. Sympathy Maxim. In formal situations there is politeness in communicating with students. In the context of Indonesian language lectures with the discussion method, class IIIA students have used the six maxims of politeness